2021
DOI: 10.2176/nmccrj.cr.2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Planned Four-stage Transforaminal Full-endoscopic Lumbar Decompression under Local Anesthesia in a Patient with Severe Comorbidity

Abstract: A 74-year-old man presented with symptoms of intermittent claudication. A diagnosis of lumbar spinal canal stenosis (LSS) at L3/4 and L4/5 was made based on the clinical and radiological findings. Bilateral lateral recess stenosis was detected at both these levels on magnetic resonance imaging (MRI) and on computed tomography (CT) scans obtained after myelography. Four nerve roots were impinged bilaterally at L4 and L5. The initial plan was to perform conventional laminectomy at L3/4 and L4/5 under general ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Full-endoscopic discectomy, which was initially developed by Yeung and Tsou for lumbar disc herniation, 6) is a minimally invasive procedure that is now used to treat foraminal stenosis and lateral recess stenosis. 1,[7][8][9] Lumbar interbody fixation can now be performed by full-endoscopic discectomy using the procedure named KLIF by Sairyo et al 2) Various types of LIF have been reported, including ALIF, LLIF, TLIF, and PLIF. There has been a recent report de-scribing the use of LLIF to treat adult spinal deformity because of its indirect decompressive effect, less surgical invasiveness and blood loss, and strong corrective force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-endoscopic discectomy, which was initially developed by Yeung and Tsou for lumbar disc herniation, 6) is a minimally invasive procedure that is now used to treat foraminal stenosis and lateral recess stenosis. 1,[7][8][9] Lumbar interbody fixation can now be performed by full-endoscopic discectomy using the procedure named KLIF by Sairyo et al 2) Various types of LIF have been reported, including ALIF, LLIF, TLIF, and PLIF. There has been a recent report de-scribing the use of LLIF to treat adult spinal deformity because of its indirect decompressive effect, less surgical invasiveness and blood loss, and strong corrective force.…”
Section: Discussionmentioning
confidence: 99%
“…Full-endoscopic discectomy, which was initially developed by Yeung and Tsou for lumbar disc herniation, 6 ) is a minimally invasive procedure that is now used to treat foraminal stenosis and lateral recess stenosis. 1 , 7 - 9 ) Lumbar interbody fixation can now be performed by full-endoscopic discectomy using the procedure named KLIF by Sairyo et al 2 )…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide range of treatable lumbar stenosis and the reported favorable clinical outcomes, the endoscopic posterior approach has attracted more and more attention. [17][18][19][20][21][22] As we all know, the outside-in technique was most accepted in the LE-ULBD surgery, 23 whose procedure involves removal of bony structure including the lamina, articular facet joint first, then the entire LF en bloc or piecemeal to expose the dura and nerve root. However, the outside-in technique has disadvantages including uncertain removal border, dura tear and nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, transforaminal FESS can be conducted with a skin incision that is only 7-8 mm (10)(11)(12)(13)(14). FESS is the best option for elderly patients with poor general condition and foraminal stenosis following OVF because it is minimally invasive and can be performed under local anesthesia (23,24). However, information on this surgical technique in the literature remains sparse (17,18,25).…”
Section: Surgical Strategy For Foraminal Stenosismentioning
confidence: 99%